Spatial Analysis of Land Degradation Susceptibility and Alternative Plants for Its Rehabilitation - Auliyani, Diah; Basuki, Tyas Mutiara; Wijaya, Wahyu Wisnu (Forum Geografi, 2019)
One of the drawbacks of developing plants for the rehabilitation of degraded land in Indonesia is the relative lack of information about species that are suited to the local conditions. Therefore, spatial information on land degradation and the plants suitable for rehabilitation is crucial. The objectives of this study were to map the susceptibility of land to degradation and to identify some alternative species for its rehabilitation. The research was conducted in Jang Watershed, Bintan Island, Kepulauan Riau Province, Indonesia. A quick assessment of land degradation was carried out to classify the degree of land susceptibility. The land suitability evaluation was conducted manually by matching the existing biophysical condition and plant growth requirements using a geographic information system. This analysis was applied for annual plants, such as Acacia mangium, Durio zibethinus, Artocarpus champeden, Theobroma cacao and Hevea brassiliensis. Furthermore, the maps of land susceptibility to degradation and species suitability were overlaid and the result was used to provide recommendations for rehabilitating the degraded land. This study showed that 22% of the Jang Watershed area can be categorised as highly susceptible to degradation. The suitability analysis illustrated that 59% of the degraded areas were suitable for Acacia mangium. The planting of fast-growing species such as Acacia mangium is expected to improve the physical, chemical and biological properties of the soil.